BEING ISLAM OUT OF FANATICISM - Wijaya, Aksin; Ahid, Nur; Irsyady, Kamran Asat (International Journal of Psychosocial Rehabilitation, 2020)
It is strongly believed that pre-Islamic Arabs were ummi and jahiliyah (ignorant). These two characters weresymbolizing the ignorance and moral decadence at that time. The Prophet Muhammad was born in that era. His mission was to solvethe problems occurred, and he successfully did it in less than twenty years of his prophetic mission. Itwas a remarkable success considering the transformation of Arabs from being ignorant and decadent to be civil and religious. This article is aimed at critically analyzing this brisk transformation, focusing on three aspects, namely, the essence of religiosity of human being with special reference of the Arabs, the reason of the triumph of Islam over polytheism and the background of labelling Arab as ummi and jahiliyah. Epistemological and historical approach was employed to address those issues.The finding showed that, firstly religiosity is fitri universally, however, it is optionally when dealing with particularities. Second, pre-Islamic Arabs readily embraced Islam revealed to Prophet Muhammad due to ethnic fanaticism, solidarity and personal quality of the Prophet himself. And third, pre-Islamic Arabs readily accepted Islam due to the adequate qualities, pre-understanding and, pre-belief.